2016
DOI: 10.1111/jcpt.12394
|View full text |Cite
|
Sign up to set email alerts
|

Significant impacts of CYP3A4*1G and CYP3A5*3 genetic polymorphisms on the pharmacokinetics of diltiazem and its main metabolites in Chinese adult kidney transplant patients

Abstract: The CYP3A4*1G and CYP3A5*3 genetic polymorphisms are closely related to the trough concentration/dose ratios and pharmacokinetics of diltiazem and its main metabolites in Chinese adult renal transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…9 This finding is closely related to the differences in the genes related to drug metabolism in different individuals, mainly those genes related to the cytochrome CYP3A metabolizing enzyme and the multiple P-gp encoded by the drug resistance gene MDR1. 10 The CYP3A4*18B mutation enhances CYP3A4 enzyme activity, leading to a decrease in the C0/D of tacrolimus in patients carrying this allele, [11][12][13] and the present study confirmed a faster metabolism in CYP3A4*18B-expressing patients than in nonexpressing patients among healthy subjects. CYP3A5*3 has a high frequency of mutation in the Chinese population; CYP3A5*3/*3 is the most common mutant, and patients with CYP3A5-expressing genotypes (*1/*1 and *1/*3) metabolize tacrolimus more rapidly than patients with CYP3A5-nonexpressing genotypes (*3/*3).…”
Section: Correlations Between Indicators and Pharmacokinetic Parameterssupporting
confidence: 80%
“…9 This finding is closely related to the differences in the genes related to drug metabolism in different individuals, mainly those genes related to the cytochrome CYP3A metabolizing enzyme and the multiple P-gp encoded by the drug resistance gene MDR1. 10 The CYP3A4*18B mutation enhances CYP3A4 enzyme activity, leading to a decrease in the C0/D of tacrolimus in patients carrying this allele, [11][12][13] and the present study confirmed a faster metabolism in CYP3A4*18B-expressing patients than in nonexpressing patients among healthy subjects. CYP3A5*3 has a high frequency of mutation in the Chinese population; CYP3A5*3/*3 is the most common mutant, and patients with CYP3A5-expressing genotypes (*1/*1 and *1/*3) metabolize tacrolimus more rapidly than patients with CYP3A5-nonexpressing genotypes (*3/*3).…”
Section: Correlations Between Indicators and Pharmacokinetic Parameterssupporting
confidence: 80%
“…In addition to the calculation results, it was discovered that the rs2242480 (C) allele was correlated with the rs776746 (C) allele, and the rs 2242480 (T) allele was also found to be correlated with the rs776746 (T) allele. The study by Zhou et al [7]. showed a strong linkage disequilibrium between CYP3A4*1G and CYP3A5*3 in the Chinese population.…”
Section: Resultsmentioning
confidence: 95%
“…It is well known that the presence of the CYP3A4*1G allele causes changes in the pharmacokinetic profile of some drugs. For example, a study by Zhou et al [7]. showed that the concentrations of diltiazem and its primary metabolites were strongly influenced by the CYP3A4*1G allele [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations